An Unusual Terrible Triad Variant Associated with an Essex-Lopresti Injury - Luis M. Salazar; Abdullah Ghali; Jose M. Gutierrez-Naranjo; Thomas L. Hand; Anil K. Dutta (Case Reports in Orthopedics)
Essex-Lopresti injuries and terrible triad injuries of the elbow are rare injuries that typically result from high-energy trauma such as falling from a height or a motor vehicle collision. However, the combination of an Essex-Lopresti injury and terrible triad injury is unique and poses a significant challenge for treatment as these injuries are independently associated with poor functional outcomes if they are not acutely diagnosed. We describe a case of a 19-year-old who presented with an unusual variant of a terrible triad injury associated with an Essex-Lopresti injury. The patient had a distal radioulnar joint (DRUJ) and elbow dislocation, a radial head and coronoid process fracture, and a distal radius fracture. Almost a reverse Essex-Lopresti, this injury was successfully managed with open reduction and repair of the distal radius, radial head, and damaged ligaments in the elbow, along with an internal joint stabilizer (IJS).